Metabo‐ and mechanoreceptor expression in human heart failure: Relationships with the locomotor muscle afferent influence on exercise responses. Issue 5 (29th March 2020) - Smith, Joshua R.; Hart, Corey R.; Ramos, Paola A.; Akinsanya, Joshua G.; Lanza, Ian R.; Joyner, Michael J.; Curry, Timothy B.; Olson, Thomas P.
Abstract : New Findings: What is the central question of this study? How do locomotor muscle metabo‐ and mechanoreceptor expression compare in heart failure patients and controls? Do relationships exist between the protein expression and cardiopulmonary responses during exercise with locomotor muscle neural afferent feedback inhibition? What is the main finding and its importance? Heart failure patients exhibited greater protein expression of transient receptor potential vanilloid type 1 and cyclooxygenase‐2 than controls. These findings are important as they identify receptors that may underlie the augmented locomotor muscle neural afferent feedback in heart failure. Abstract: Heart failure patients with reduced ejection fraction (HFrEF) exhibit abnormal locomotor group III/IV afferent feedback during exercise; however, the underlying mechanisms are unclear. Therefore, the purpose of this study was to determine (1) metabo‐ and mechanoreceptor expression in HFrEF and controls and (2) relationships between receptor expression and changes in cardiopulmonary responses with afferent inhibition. Ten controls and six HFrEF performed 5 min of cycling exercise at 65% peak workload with lumbar intrathecal fentanyl (FENT) or placebo (PLA). Arterial blood pressure and catecholamines were measured via radial artery catheter. A vastus lateralis muscle biopsy was performed to quantify cyclooxygenase‐2 (COX‐2), purinergic 2X3 (P2X3 ), transient receptor potential vanilloid type 1 (TRPV 1), acid‐sensing ion channel 3 (ASIC3 ), Piezo 1 and Piezo 2 protein expression. TRPV 1 and COX‐2 protein expression was greater in HFrEF than controls (both P  < 0.04), while P2X3, ASIC3, and Piezo 1 and 2 were not different between groups (all P  > 0.16). In all participants, COX‐2 protein expression was related to the percentage change in ventilation ( r  = −0.66) and mean arterial pressure (MAP) ( r  = −0.82) (both P  < 0.01) with FENT (relative to PLA) during exercise. In controls, TRPV 1 protein expression was related to the percentage change in systolic blood pressure ( r  = −0.77, P  = 0.02) and MAP ( r  = −0.72, P  = 0.03) with FENT (relative to PLA) during exercise. TRPV 1 and COX‐2 protein levels are elevated in HFrEF compared to controls. These findings suggest that the elevated TRPV 1 and COX‐2 expression may contribute to the exaggerated locomotor muscle afferent feedback during cycling exercise in HFrEF. Abstract :